2022
DOI: 10.31083/j.jin2104120
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Pain Subtypes among Patients with Parkinson's Disease

Abstract: Background: To determine the influence of gender on the different pain subtypes experienced by patients with Parkinson's disease (PD). Methods: Two hundred patients with PD were recruited for this research. Demographic features for all patients were recorded, as well as clinical data on age, disease duration, levodopa equivalent daily dose (LEDD), and scores for Unified Parkinson's Disease Rating Scale-III (UPDRS III), Hoehn-Yahr Scale (H&Y), King's Parkinson's disease Pain Scale (KPPS), Pittsburgh Sleep Quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…[14,29] Our study showed high prevalence and severity of pain musculoskeletal, fluctuation-related and discoloration, edema/ swelling domains in females but with similar total KPPS-Arabic in consistent to study by Chaudhuri et al [9,23] Similarly, previous studies reported more frequent musculoskeletal, [23] and discoloration, edema/ swelling pains, and higher scores of chronic pain, fluctuation-related pain and orofacial pain. [35] In the present study, we also found that pain in PWP negatively affected their QoL as assessed by PDQ-39 in agreement with previous studies. [25] Using KPPS-Arabic, we were able to further identify the types of pain, especially influencing QoL in those patients, which were mainly fluctuation-related pain and nocturnal pain followed by chronic and discoloration pains, but not musculoskeletal pain.…”
Section: Discussionsupporting
confidence: 93%
“…[14,29] Our study showed high prevalence and severity of pain musculoskeletal, fluctuation-related and discoloration, edema/ swelling domains in females but with similar total KPPS-Arabic in consistent to study by Chaudhuri et al [9,23] Similarly, previous studies reported more frequent musculoskeletal, [23] and discoloration, edema/ swelling pains, and higher scores of chronic pain, fluctuation-related pain and orofacial pain. [35] In the present study, we also found that pain in PWP negatively affected their QoL as assessed by PDQ-39 in agreement with previous studies. [25] Using KPPS-Arabic, we were able to further identify the types of pain, especially influencing QoL in those patients, which were mainly fluctuation-related pain and nocturnal pain followed by chronic and discoloration pains, but not musculoskeletal pain.…”
Section: Discussionsupporting
confidence: 93%
“…However, the period-prevalence in the current study was lower than in other regional studies: 79.6% in Bulgarian patients and 88.6% in Mexico City patients ( 23 , 26 ). Reasons for the lower pain prevalence found in the current study could be attributed to the inclusion of majority mild disease severity (H & Y II) as well as the study sample comprising mainly males, as sources indicate a lower reporting of pain amongst men ( 27 ). In addition, since the current study was founded on a clinical trial, subjects with pain may be less interested in subscribing to balance training interventions, as it may provoke their pain.…”
Section: Discussionmentioning
confidence: 64%
“…Pain is twice as frequent in PD patients than in individuals without PD, even after adjustment for osteoarticular comorbidities (Negre-Pages et al, 2008). Pain in PD is more frequent in females, although the causes for this are unclear (Gao et al, 2022). Pain can appear anytime during the disease and can be present before diagnosis.…”
Section: Microbiota In Pain and Parkinson's Diseasementioning
confidence: 99%